Faktor-Faktor yang mempengaruhi Perilaku Belanja Online pada E-Commerce Shopee - Shelly Lau; Wibisono Soediono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to know the influence of Relative Advantage, E-WOM, and Trust toward Attitudes towards Online Shopping to E-Commerce Shopee. The research design used descriptive research and causality research and variables are measured with 5 points Likert scale. This research collected by questionnaire by used primary data. The sampling in this study was purposive sampling and used 120 respondents. The data analysis techniques used in this study were descriptive statistics, quality tests, assumption tests, and hypothesis testing. The result of this study indicate that relative advantage, e-wom, and trust have an influence to attitudes towards online shopping.